شهادة النساء في العقوبات في الشريعة الإسلامية - النجار، مزاحم مهدي إبراهيم (مركز البحث وتطوير الموارد البشرية (رماح) بالتعاون جامعة القرآن الكريم وتأصيل العلوم بالسودان, 2022)
إن من خصائص الشريعة الإسلامية أنها جاءت بأحكام صالحة لكل زمان ومكان، ومن المعلوم أيضا أن الله سبحانه وتعالى قد كرم المرأة كما كرم الرجل قال تعالى (لَقَدْ كَرَّمْنَا بَنِي آَدَمَ) وبني أدم يشمل الرجل والمرأة وقي السنة النبوية أحاديث كثيرة حول تكريم المرأة وإعطائها مكانة مرموقة منها قوله صلى الله عليه وسلم (ما أكرمهن إلا كريم وما أهانهن إلا لئيم) ومن تكريم المرأة في الإسلام انه خفف عنها بعض الأمور لا تقليلا من قيمتها ولكن حفاظا عليها وتكريما لها وإبعادها عن كل ما يؤثر عليها ومع ذلك فان أعداء الإسلام ومن تتلمذ على أيديهم من المسلمين الذين لم يفهموا الإسلام الفهم الصحيح أو من كانت لهم نوايا سيئة شككوا فيما جاء به الإسلام من أحكام وقيم مدعين مرة باسم المساواة ومرة باسم الحقوق ومرة ثالثة باسم العدالة ومزاعم باطلة ظاهرها مساندة المرأة والوقوف معها، وحقيقتها إذلال المرأة والنيل من عزتها وكبريائها وشموخها لتكون ذليلة بأيديهم يحركونها كيفما شاءوا باسم الجرية والمساواة وغيرها ومن هذه الأمور التي أردت تسليط الضوء عليها وإزاحة الشكوك الواهية حولها وبيان الحقيقة الناصعة لأوامر الدين الإسلامي هي شهادة النساء في العقوبات. لقد قمت بذكر آراء الطرفين وأدلتهم ومن ثم مناقشتها مناقشة علمية للوصول إلى الحقيقة التي غابت عن من يدعون أنهم يدافعون عن حقوق المرأة لقد اقتضت طبيعة البحث أن يكون على مقدمة وخمسة مباحث وخاتمة وكالاتي: المقدمة: وفيها أهمية الموضوع وسبب الكتابة فيه المبحث الأول: مفاهيم العنوان المبحث الثاني: حكم شهادة النساء في العقوبات في الشريعة الإسلامية المبحث الثالث: شهادة النساء ي الحدود المبحث الرابع: شهادة النساء في القصاص المبحث الخامس: شهادة النساء على جرائم التعزير الخاتمة وفيها أهم النتائج One of the characteristics of Islamic sharia is that it came with rulings valid for every time and place It is also known that God Almighty has honored the woman as he honored the man, the Almighty said (And We have honored the children of Adam) and the children of Adam include both men and women. In the Sunnah of the Prophet, there are many hadiths about honoring women and giving them a prominent position, including his saying: The Prophet, may God’s prayers and peace be upon him, (No one honors them except the generous, and none humiliates them but the mean one) Among the honoring of woman in Islam is that it eases some things for her not in order to reduce her value but in order to preserve and honor her and keep her away from everything that affects her Nevertheless, the enemies of Islam and the Muslims who were taught by them from among the Muslims who did not properly understand Islam or who had bad intentions questioned the rules and values that Islam brought about once pretending In the name of equality, once in the name of rights, and a third time in the name of justice, and false allegations that appear to support women Standing with it, and its reality is to humiliate the woman and undermine her dignity, pride and loftiness, so that she becomes humiliated by their own hands. They move her however they want in the name of freedom, equality and others. One of these matters that I wanted to shed light on, remove the flimsy doubts about it, and clarify the clear truth of the orders of the Islamic religion is the testimony of women in punishment. I have mentioned the views and evidence of the two parties and then discussed them in a scientific discussion to reach the truth that was absent from those who claim to defend women's rights The nature of the research required that it be an introduction, five discussions, and a conclusion as follows: Introduction: It contains the importance of the topic and the reason for writing in it The first topic: Concepts of the title The second topic: The ruling on women’s testimony in punishments in Islamic Sharia The third topic: the testimony of women in the border The fourth topic: the testimony of women in retribution The fifth topic: the testimony of women on the crimes of reprimand The conclusion contains the most important results
Keywords: الشريعة الإسلامية -- شهادة النساء -- العقوبات -- الأحاديث النبوية -- المرأة في الإسلام